Fenofibrate treatment during withdrawal reverses symptoms of ethanol-induced depression in male rats - León, Marcelo; Vásquez-Ulloa, Camila; Marambio-Ruiz, Lucas; Pérez-Reytor, Diliana; Karahanian, Eduardo (Frontiers in Pharmacology, 2025)
Alcohol use disorder (AUD) and major depression frequently co-occur, both involving significant neuroinflammatory components. Current treatments are often ineffective in addressing AUD-related depression, highlighting the need for novel therapeutic approaches. Previous studies showed that fenofibrate, a peroxisome proliferator-activated receptor alpha (PPAR-α) agonist, reduces voluntary alcohol intake and attenuates neuroinflammation and oxidative stress in alcohol-preferring rats. This study investigated whether fenofibrate administered during alcohol withdrawal could alleviate ethanol-induced depressive symptoms and neurobiological alterations. Male rats received ethanol (1 g/kg, i. p.) on alternate days for 3 weeks; controls received saline. During a 2-week withdrawal period, half of the ethanol-treated rats received fenofibrate (50 mg/kg/day) for the final 5 days. Behavioral assessments included the open field, tail suspension, and sucrose intake tests. RT-qPCR evaluated proinflammatory cytokine and brain-derived neurotrophic factor (BDNF) expression in the prefrontal cortex (PFC) and hippocampus, while Golgi staining assessed dendritic arborization. Ethanol exposure increased anxiety and immobility in behavioral tests, consistent with depressive-like behaviors, and elevated TNF-α, IL-1β, and IL-6 levels. Fenofibrate reversed these behavioral and molecular effects, normalized PFC BDNF expression, and partially restored dendritic complexity. However, ethanol-induced reductions in sucrose intake after withdrawal—reflecting anhedonia—were not reversed by fenofibrate. These findings suggest that fenofibrate mitigates ethanol-induced depressive-like behaviors and neurobiological dysfunctions through anti-inflammatory and neuroprotective mechanisms. Given its established clinical use and safety profile as an FDA-approved drug, fenofibrate shows promise as a translational therapeutic adjunct for treating depression in individuals with AUD.